Effect of food deprivation on the hypothalamic gene expression of the secretogranin II-derived peptide EM66 in rat. Issue 16 (8th November 2017) - Trebak, Fatima; Dubuc, Isabelle; Picot, Marie; Alaoui, Abdelilah; Leprince, Jérôme; Prévost, Gaëtan; Anouar, Youssef; Magoul, Rabia; Chartrel, Nicolas
Abstract : EM66 is a peptide derived from the chromogranin, secretogranin II ( SG-II ). Recent findings in mice indicate that EM66 is a novel anorexigenic neuropeptide that regulates hypothalamic feeding behavior, at least in part, by activating the POMC neurons of the arcuate nucleus. The present study aimed to investigate the mechanism of action of EM66 in the control of feeding behavior and, more specifically, its potential interactions with the NPY and POMC systems in rat. We analyzed by Q-PCR the gene expression of the EM66 precursor, SG-II, in hypothalamic extracts following 2, 3, or 4 days of food deprivation and compared it with the expression levels of the two major neuropeptidergic systems, that is, POMC and NPY, modulating feeding behavior. Our results show that fasting for 2 and 3 days has no effect on SG-II mRNA levels. However, 4 days of food deprivation induced a significant alteration in the expression levels of the three genes studied, with a significant increase in SG-II and NPY mRNAs, and conversely, a significant decrease in POMC mRNA. These data indicate that the EM66 gene expression is modulated by a negative energy status and suggest interactions between EM66 and NPY to regulate food intake through the POMC system.